Analisis Pertumbuhan dan Ketimpangan Regional Antar Kabupaten-Kota di Provinsi Kalimantan Selatan dan Kalimantan Tengah Tahun 2010-2016: Sebuah Perbandingan - Harris, Faisal; Ahmad Yunani (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This study aims to analyze how the Comparison of Income Inequality between Regions, Classification of Region, and Level of Interaction between Region in South Kalimantan and Central Kalimantan Provinces. The data used in this research is Secondary Data obtained from the Central Statistics Agency. The analytical techniques used are Williamson Index, Classen Typology, and Gravity Model.The results showed that income inequality between regions in South Kalimantan was higher than Central Kalimantan. Regional Classification in South Kalimantan is dominated by Developing Regions, while Central Kalimantan is dominated by Relatively Lagging Regions. And based on the Gravity Model, South Kalimantan with the Reference City of Banjarmasin has a higher Gravity Index value than Central Kalimantan with the Reference City of Palangka Raya.